Mechanisms of mitogen-activated protein kinase inhibition by parathyroid hormone in osteoblast-like cells - Hömme, Meike; Schmitt, Claus P.; Mehls, Otto; Schaefer, Franz (Journal of the American Society of Nephrology, 2004)
Parathyroid hormone (PTH) dose dependently inhibits growth factor- and stress-induced osteoblast proliferation via inactivating mitogen-activated protein kinase (MAPK) signaling pathways. Osteoblasts have recently been shown to express MAPK phosphatase (MKP)-1, a dual-specific phosphatase inactivator of MAPK. Investigated was the role of MKPs in the PTH-induced attenuation of MAPK and Jun N-terminal kinase (JNK) signaling in osteoblast-like UMR106-01 cells.